Investigation into the highly efficient Artemisia absinthium-silver nanoparticles composite as a novel environmentally benign corrosion inhibitor for mild steel in 1M HCl. Issue 23 (17th December 2022) - Mobin, Mohammad; Ahmad, Irfan; Shoeb, Mohd
Abstract: A nano-scale Artemisia absinthium extract-silver nanoparticles composite (AAE-AgNPs) was biosynthesised and tested as a novel, eco-friendly corrosion inhibitor for mild steel (MS) in 1M HCl. AAE-AgNPs was characterised using FTIR, UV–visible, XRD, DLS, and TEM techniques. UV–Vis determined the SPR signal of AgNPs at 408 nm while XRD defined the lattices planes (111), (200), (220), and (311) corresponding to FCC structure of AgNPs. DLS and TEM confirmed the integration of AgNPs in the extract. Corrosion inhibition efficiency (I.E) of AAE-AgNPs composite was evaluated engaging gravimetric, PDP, and EIS techniques. The gravimetric analysis was conducted over temperatures 30 °C–60 °C, and it revealed that AAE-AgNPs composite exhibited highest I.E of 93.74% at 30 °C at a concentration of 500 ppm. EIS results revealed the formation of an inhibitive barrier film between MS and 1 M HCl, while PDP analysis described that AAE-AgNPs is behaving as a mixed type inhibitor, i.e. it is controlling both anodic dissolution of MS and cathodic evolution of H2 . Values of Δ Gads obtained near −20 kJ mol −1 indicate that physisorption is the most likely scenario of adsorption. FTIR and UV–Vis studies predicted the interaction occurring between MS and AAE-AgNPs while SEM established improved surface morphology of MS in inhibited medium and appearance of O and Ag peak at 3 KeV under EDAX spectrum confirmed the formation of adsorbed inhibitive film of AAE-AgNPs on MS. Highlights: Artemisia absinthium -silver nanoparticles composite (AAE-AgNPs) was synthesised and characterised by UV, FTIR, XRD, DLS, and TEM AAE-AgNPs was investigated as effective inhibitor by WL, EIS, PDP, FTIR, UV, and SEM/EDAX techniques AAE-AgNPs proved an efficient green inhibitor exhibiting inhibition efficiency of 93.74% at 500 ppm Conducted Immersion and TGA study displayed the biochemical and thermal stability of AAE-AgNPs The adsorption of AAE-AgNPs on MS conformed to Langmuir adsorption isotherm model